An extreme change in structural and optical properties of indium oxynitride deposited by reactive gas-timing RF magnetron sputtering - Sungthong, A.; Porntheeraphat, S.; Poyai, A.; Nukeaw, J. (My University, 2008)
The indium oxynitride (InON) films were achieved by reactive RF magnetron sputtering indium target which has the purity of 99.999% with a novel reactive gas-timing technique. The structural, optical and electrical properties in a series of polycrystalline InON films affected by gas-timing of reactive N 2 and O 2 gases introduced to the chamber were observed. The X-ray photoelectron spectroscopy revealed that the oxygen content in thin films that compounded to indium and nitrogen, which increased from 10% in indium nitride (InN) to 66% in indium oxide (In 2 O 3 ) films. The X-ray diffraction peaks show that the phase of deposited films changes from InN to InON and to In 2 O 3 with an increasing oxygen timing. The hexagonal structure of InN films with predominant (0 0 2) and (0 0 4) orientation was observed when pure nitrogen is only used as sputtering gas, while InON and In 2 O 3 seem to demonstrate body-center cubic polycrystalline structures depending on gas-timing. The surface morphologies investigated from atomic force microscope of deposited films with varying gas-timing of O 2 :N 2 show indifferent. The numerical algorithm method was used to define the optical bandgap of films from transmittance results. The increasing oxygen gas-timing affects extremely to the change of crystallinity phase from InN to InON and to In 2 O 3 , the increase of optical bandgap from 1.4 to 3.4 eV and the rise of sheet resistance from 15 Ω/□ to insulator. © 2008 Elsevier B.V. All rights reserved.
Keywords: Indium nitride; Indium oxide; Indium oxynitride; Reactive gas-timing; RF magnetron sputtering